Wavelength Switchable Mode-Locked Fiber Laser With Tapered Two-Mode Fiber - Liqin Xie; Fang Fang; Bing Sun; Mengmeng Chen; Zuxing Zhang (IEEE Photonics Journal, 2019)
We propose and demonstrate a wavelength switchable mode-locked Erbium-doped fiber laser with carbon nanotubes for mode-locking and a tapered two-mode fiber (TTMF) based filter for wavelength selection. The TTMF based filter constructed with single-mode fiber-TTMF-single-mode fiber configuration, features smooth interference spectrum. It is attributed to that only two modes are involved into the interference in the specially designed TTMF, which is confirmed by both simulations and experiments. Moreover, the free spectral range (FSR) of the TTMF based filter can be arbitrarily chosen by controlling the taper diameter. Depending on the FSR of the TTMF based filter, the central wavelengths of the mode-locking operation of the Erbium-doped fiber laser based on carbon nanotubes can be switched between two wavelengths with FSR of 8.5 nm and three wavelengths with FSR of 3.1 nm, respectively. This fiber laser is flexible source for various applications.